Identifying Italian ciphers from continuous-figure ciphertexts (1593). Issue 1 (2nd January 2019) - Tomokiyo, Satoshi
Abstract: Italian ciphers of the 16th century often used Arabic figures written continuously without a break. The first step in reading such a ciphertext is to split the continuous sequence of figures into individual cipher symbols. However, this is not straightforward for codebreakers when the cipher symbols are not of fixed length. I succeeded in splitting the continuous sequence into individual symbols for three undeciphered ciphertexts from 1593, which all turned out to employ different schemes. Once the figures were broken into individual groups, the ciphers were simple enough to allow preliminary decipherment without knowledge of Italian.